PROFESIONALISME GURU DITINJAU DARI LATAR BELAKANG PENDIDIKAN DAN PENGALAMAN MENGAJAR : Penelitian Pada Guru-Guru SD se-Kecamatan Andong Kabupaten Boyolali Tahun 2001 - Sutoyo, Sugiaryo & (paedagogia, 2003)
ABSTRACTresearch was conducted in Andong Sub District, Boyolali Regency, in the year of 2001. The aim of the research was to find out wether teacher’ profesionalism influenced by either their education background, their teaching experience, or by the interaction effect of both those independent variables. Survey Population covered all of the elementary schools teachers located in Andong. Eigthy two teachers were sampled randomly proportional stratified. Document studies, interview, and questionmatres were employed to collect data. analysis of variable model : Xijk= +ai+ j+a ij+ ijk were used to test hyphotesis. The results indicated that teachers’ proffesionalism were influenced by either their educational background, their teaching ecperiences, or by the interaction effect of both those two indepencent variables. This showed by the findings that Fa>F(2;73;0,01); Fb(2;2;73:0,01); Fab>F(4;73:0,01). Thus, the hyphotesis was upheld.Kata Kunci : Profesionalisme guru, latar belakang pendidikan, pengalaman mengajar.